Employing Social Network Analysis to Examine the Social Participation of Students Identified as Having Special Educational Needs and Disabilities. Issue 4 (3rd July 2020) - Mamas, Christoforos; Schaelli, Giovanna Hartmann; Daly, Alan J.; Navarro, Henar R.; Trisokka, Lambri
ABSTRACT: The number of students with identified Special Educational Needs and Disabilities (SEND) in mainstream schools has been rising in the last three decades, primarily due to policy changes promoting inclusive education. However, many of these students remain socially isolated despite expectations that inclusion may lead to enhanced outcomes, particularly social outcomes. This paper draws on a study conducted in three countries; Cyprus, Spain, and Switzerland. A critical case study design, grounded in social capital theory, was adopted to examine the concept of social participation from a social network perspective in six Grade 4 classrooms, two in each country. Data were collected through 109 network surveys. Network maps for each classroom were developed, and social network measures were calculated. The findings from each case/classroom were encouraging in terms of the social participation of students with SEND and have provided a layer for understanding social responsiveness and inclusion of each classroom. The social participation for many students with SEND was found to be comparable to peers without SEND.